2019
DOI: 10.4149/neo_2018_180522n333
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent oligometastatic transitional cell bladder carcinoma: is there room for radiotherapy?

Abstract: This paper presents a retrospective report on radiotherapy (RT) in the oligometastastic recurrence of bladder cancer. Thirteen patients treated for low-volume metastatic transitional cell urinary bladder carcinoma (TCC) were reviewed, with the primary endpoint to evaluate the safety and efficacy of RT, proposed as an alternative to systemic treatment and/or to defer commencement of systemic therapy. The inclusion criteria were: patients who received RT without other local/ systemic therapy for oligometastatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 26 publications
0
24
0
1
Order By: Relevance
“…Further studies by Maing et al 14 have evaluated the role of radiotherapy in treating BM in mUC and demonstrated a survival advantage when radiation doses were given as an equivalent dose in 2-Gy fractions of ⩾20 Gy. In regard to oligometastatic disease (⩽3 lesions), durable disease control in a select group of patients with metastasis-directed stereotactic body radiation therapy (SBRT) 18 was seen, although a paucity of data exists in this space. Multikinase inhibitors (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies by Maing et al 14 have evaluated the role of radiotherapy in treating BM in mUC and demonstrated a survival advantage when radiation doses were given as an equivalent dose in 2-Gy fractions of ⩾20 Gy. In regard to oligometastatic disease (⩽3 lesions), durable disease control in a select group of patients with metastasis-directed stereotactic body radiation therapy (SBRT) 18 was seen, although a paucity of data exists in this space. Multikinase inhibitors (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…3 der 13 oligometastasierten Patienten waren nach 25 Monaten ohne Krankheitsnachweiß. Somit kann ein oligometastasiertes Blasenkarzinom effektiv mittels metastasengezielter Radiatio behandelt werden [ 20 ].…”
Section: Rationale Für Metastasengezielte Therapieunclassified
“…An Italian single institution retrospective review of stereotactic irradiation of synchronous lymph node only metastases from urothelial carcinoma reported a local control rate of 100% at 2 months with 6 out of 14 target lesions showing partial response and 8 remaining stable. The median treated lymph node PFS was 11.4 months (95%CI: 3.4-19.4), but overall PFS was 2.9 months (95%CI: 2.6-3.1) and OS was 14.9 months (95%CI: 12.3-17.5) [84] . SBRT using Cyberknife stereotactic radiotherapy to bone, lung and lymph node metastases in urothelial cancer has been reported with one-third remaining disease-free at 30 months with no major toxicity [85] .…”
Section: Distant Metastasis-directed Therapymentioning
confidence: 95%